2005
DOI: 10.1103/physrevb.72.064203
|View full text |Cite
|
Sign up to set email alerts
|

Core-level shifts in fcc random alloys: A first-principles approach

Abstract: First-principles theoretical calculations of the core-level binding-energy shift ͑CLS͒ for eight binary facecentered-cubic ͑fcc͒ disordered alloys, CuPd, AgPd, CuNi, NiPd, CuAu, PdAu, CuPt, and NiPt, are carried out within density-functional theory ͑DFT͒ using the coherent potential approximation. The shifts of the Cu and Ni 2p 3/2 , Ag and Pd 3d 5/2 , and Pt and Au 4f 7/2 core levels are calculated according to the complete screening picture, which includes both initial-state ͑core-electron energy eigenvalue͒… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
65
0
2

Year Published

2006
2006
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(78 citation statements)
references
References 58 publications
11
65
0
2
Order By: Relevance
“…(7)] or two points, while the selection of three gives results very similar to the use of even further points. In a comparison between the transition state method and complete screening picture for the CLS in disordered alloys, it was found that the two computation schemes in most cases closely follow each other, however not with identical results [18].…”
Section: Transition State Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…(7)] or two points, while the selection of three gives results very similar to the use of even further points. In a comparison between the transition state method and complete screening picture for the CLS in disordered alloys, it was found that the two computation schemes in most cases closely follow each other, however not with identical results [18].…”
Section: Transition State Methodsmentioning
confidence: 99%
“…Notice that while in principle Janak's theorem is only valid for the highest occupied electron, it has however also been successfully applied to core states [18,[37][38][39]. In the practical calculations, a fractional electron is promoted to the valence band leaving a fractional core-hole, ensuring charge neutrality and a full screening in similarity with the complete screening picture.…”
Section: Transition State Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The Au 4f7/2 core level (not shown) is also 137 shifted towards lower BE by ~0.6 eV for Pd3Au relative to pure Au. A discussion of the core level 138 shifts in the PdAu-alloy is beyond the scope of the present work, but has been previously been7 addressed by Olovsson et al [54]. Since the surface oxide incorporates Pd atoms only, the √5 oxide 140 peak positions are similar for Pd(100), Pd3Au(100) and Pd75Ag25(100).…”
mentioning
confidence: 84%